Communication skills in the learning process of Veterinary Pathophysiology. The experience at the Veterinary Faculty of Lugo - Cristina Castillo Rodríguez; Ángel Abuelo Sebio; Joaquín Hernández Bermúdez (Universitat Politècnica de València, 2015)
Universitary teaching has been modified due to changes in the society demands: look  for  information,  critical  analysis, communication  skills,  cooperation  and determination  to  overcome  problems. These values are not commonly covered by the discipline. But society demands not only knowledge, but also other skills necessary for the well development of professional activity. To encourage faculty members about student leadership, must seek  teaching  strategies  that  stimulate them, a difficult task in several disciplines in  Health  Science  areas.  In  this  article two models of theoretical and practical teaching are discussed in the scenario of the mandatory subject General Pathology (Veterinary degree): cooperative learning(based in the PBL system) and a workshopbased  also  in  PBL  system  and  using simulated situations where students are faced with a clinical case in real conditions, including  the  presence  of  a  client  / owner and market prices for the services. Students  respond  positively  within  a framework of stimulation being capable of working together, solve problems, realizing the importance of communication skills in the development of their future career.  This forces the teacher to revitalize their teaching  according  to  society  demands that needs more skills from a student than merely knowledge acquisition.